Mitos bíblicos e greco-romanos nas charges de Belomonte: alegorias do totalitarismo - Lopes, Marihá Mickaela Neves Rodrigues (2024)
This Doctoral research aims to interpret and analyze the biblical and greco-roman myths present in satirical cartoons by the brazilian caricaturist Benedito Bastos Barreto (1896-1947), better known as Belmonte. The thesis investigates the parodic issue of myths and the way in which dialogue, present in Belmonte’s visual narratives, contributes to an allegorical vision of the Second World War period. The satirical cartoons, in addition to summarizing that event from the “age of extremes”, as Eric Hobsbawn postulates, purge the uneasiness related to the conflict, by carnivalizing the image of different personalities and promoting laughter. In its structure, this work presents introductory aspects related to the conceptualization of the satirical cartoon, highlights the intertwining of the artist’s life and work, emphasizes the importance of biblical and greco-roman mythology, as well as interprets and analyzes some of Belmonte’s visual narratives. The thesis is supported by bibliographical research. Our reflections on greco-roman mythology are anchored in Joseph Campbell, Mircea Eliade and Raphael Patai. With regard to biblical mythology, we rely on the studies of Robert Alter, Frank Kermode, Karen Armstrong, and Fernanda Sylvestre. Regarding carnivalization and allegory, we seek the studies of Mikhail Bakhtin, João Adolfo Hansen, Flávio Kothe, Carlos Ceia, and Lucas Gilnei Pereira de Melo. As for totalitarianism, we are based on the researches of Hannah Arendt and Umberto Eco. From the analyses, we can recognize that Belmonte, with his irreverent satirical cartoons and a reinterpretation of biblical and greco-roman myths, not only makes the reader laugh at dictators and their excesses, but also at totalitarian regimes.